THE INFLUENCE OF DIGITALIZATION ON THE GLOBAL PROFESSIONAL TRANSFORMATION OF THE LABOR FORCE - RUMIANTSEV, ANATOLII; KOVBYCH, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the main directions of the impact of digitalization on the global professional transformation of the workforce. The main attention is paid to structural problems of employment, labor market reform and its segmentation, consequences of introduction of automatic telephone systems, computer automation of production, processes of interaction of virtual workers, expansion of electronic workplaces, gender tendencies in digitalization of labor force and electronic work tools. Actions to eliminate illegal migration and reduce the share of the informal economy are considered and proposed. In the process of global professional transformation of the labor force, the system of values changes, material things are replaced by intangible ones. Informatization and intellectualization of the economy and social life is becoming a major driver that requires highly educated, highly skilled workers, as well as favorable ways to create favorable conditions for the optimal functioning of the single labor market. After all, the transformation of the labor market in the world depends on the influence of a wide range of factors and is characterized by a number of features. The change in demand for labor is determined by structural changes in national economies, the development of which is largely due to the deepening of globalization processes. Transformational processes in the international labor market and changes in the structure of employment remain little studied, and therefore are quite relevant today. Particular scientific attention needs to be paid to issues that are directly related to the assessment of qualitative changes in the functioning of the labor force and reflect the current international trends in its genesis in the context of digitalization.Theoretical and factual basis of this research is also the peculiarities of regulation and operation of the labor market in the most developed integration group such as the European Union (EU). First of all, the significant increase in the number of normative and legal documents regulating the legal basis for the use of the labor market in the EU countries and aimed at its reform is noteworthy.
Keywords: labor force; globalization; world labor market; digitalization; global digital economy; digital technologies; labor force transformation